Conformable Euler's theorem on homogeneous functions. Issue 5 (1st July 2019) - Martínez, Francisco; Martínez‐Vidal, Inmaculada; Paredes, Silvestre
Abstract : Recently, the conformable derivative and its properties have been introduced. In this paper, we propose and prove some new results on the conformable multivariable fractional calculus. We introduce a conformable version of classical Euler's theorem on homogeneous functions. Furthermore, we are extending the aforementioned result for higher‐order partial derivatives.